SAT-367 A Case Series: Discovery of Parathyroid Carcinoma During Parathyroidectomy for Primary Hyperparathyroidism - Gazda, Chellse (J Endocr Soc, 2020)
Introduction: Parathyroid carcinoma is rare and represents <1% of patients diagnosed with hyperparathyroidism (1). Clinical Cases: We present two cases of incidentally diagnosed parathyroid carcinoma during parathyroidectomy for primary hyperparathyroidism. A 69-year-old female was referred for hypercalcemia of 10.7 mg/dL (normal range 8.4-10.2). She had bone pain, fatigue, and mild depression. She was taking triamterene-hydrochlorothiazide, vitamin D 2000 international units daily, and 1 caltrate daily. Her thiazide diuretic was discontinued, and a repeat calcium was 9.5 mg/dL with a PTH of 79 pg/mL (normal range 14-64). Vitamin D and renal function were normal. A 24 hour urine calcium was elevated at 706 mg/24 hours (normal range 100-321). A bone density revealed osteopenia. Based on the high urine calcium, a thyroid ultrasound was completed and showed an enlarged right parathyroid gland. Intraoperatively, the surgeon found a superior parathyroid gland adherent to the local soft tissues with recurrent laryngeal nerve entrapment. The right superior parathyroid and right thyroid lobe were resected. Pathology demonstrated an infiltrating parathyroid carcinoma. Postoperative monitoring has included: calcium, creatinine, PTH and neck ultrasound every six months without evidence of recurrence. A 79-year-old man was referred for an approximate 18-month history of hypercalcemia. He had a prior kidney stone and constipation. He was not on calcium supplementations or thiazides. On lab testing calcium was 11.0 mg/dl with prior levels of 11.7 mg/dl. PTH was 246 pg/ml and vitamin D was 20.1 ng/ml (normal range 30-80). Imaging was obtained for parathyroid localization. A neck ultrasound and nuclear medicine study showed a right inferior parathyroid adenoma. A bone density revealed osteoporosis. Intraoperatively, the surgeon found a bilobed parathyroid extending intrathyroidal and adherent to the recurrent laryngeal nerve. The right inferior parathyroid, right thyroid lobe, and isthmus were resected. Pathology was consistent with parathyroid carcinoma. The patient had recurrent laryngeal nerve damage with persistent hoarseness postoperatively. Clinical Lessons: Patients with parathyroid carcinoma typically present with symptomatic hypercalcemia with mean levels of 13.5-14 mg/dL and mean PTH values 8.7 times the upper limit of normal (1). Given the rarity of the condition, there are no guidelines for surveillance (1). These cases highlight atypical, mild, and early presentations of an unusual and typically aggressive disease and serve as an example of how to monitor for recurrence. Reference: 1- Stack BC, Bodenner DL. Medical and Surgical Treatment of Parathyroid Diseases An Evidence-Based Approach. Switzerland: Springer, Cham; 2017.http://link.springer.com/chapter/10.10 07/978-3-319-26794-4_31#enumeration. Accessed November 3, 2019.